Patient-Centered Communication to Address Young Adult Breast Cancer Survivors' Reproductive and Sexual Health Concerns. Issue 13 (10th November 2021) - Gorman, Jessica R.; Drizin, Julia H.; Smith, Ellie; Flores-Sanchez, Yurissa; Harvey, S. Marie
ABSTRACT: Women faced with a diagnosis of breast cancer as young adults commonly experience negative effects of cancer and cancer treatment on their reproductive and sexual health (RSH) that are inadequately addressed by their healthcare providers (HCPs). The objectives of this study were to 1) identify approaches to improving RSH communication from YA breast cancer survivors' perspectives, 2) identify facilitators and barriers to the approaches identified, and 3) identify specific strategies to improve patient-centered RSH communication. We conducted individual telephone interviews with 29 women who were diagnosed with breast cancer under age 40 years. We used a grounded theory approach to identify themes, and explored how the themes related to the PCC framework to elucidate specific strategies for improving communication. Three main themes emerged: 1) Normalizing and integrating assessment of RSH concerns; 2) HCP conveying genuine caring and investment; and 3) Improving accessibility of comprehensive RSH services after cancer. Results revealed concrete strategies for improving patient-centered RSH communication at the patient-provider and health system levels. These included reminding patients that RSH concerns are common, routinely asking about RSH, using active listening, and connecting patients to HCP who can address their RSH concerns.